Delivery of Agents Into Articular Cartilage With Electric Spark-Induced Sound Waves - García Pérez, Alejandro; Nieminen, Heikki J.; Finnilä, Mikko; Salmi, Ari; Pritzker, Kenneth P. H.; Lampsijärvi, Eetu; Paulin, Tor; Airaksinen, Anu J.; Saarakkala, Simo; Hæggström, Edward (Frontiers in Physics, 2018)
Localized delivery of drugs into articular cartilage (AC) may facilitate the development of novel therapies to treat osteoarthritis (OA). We investigated the potential of spark-gap-generated sound to deliver a drug surrogate, i.e. methylene blue (MB), into AC. In-vitro experiments exposed bovine AC samples to either simultaneous sonication and immersion in MB (Treatment 1; n = 10), immersion in MB after sonication (Control 1; n = 10), solely immersion in MB (Control 2; n = 10), or neither sonication nor immersion in MB (Control 3; n = 10). The sonication protocol consisted of 1000 spark-gap -generated pulses. Delivery of MB into AC was estimated from optical absorbance in transmission light microscopy. Optical absorbance was significantly greater in the treatment group up to 900 µm depth from AC surface as compared to all controls. Field emission scanning electron microscopy (FESEM), histological analysis, and digital densitometry (DD) of sonicated (n = 6) and non-sonicated (n = 6) samples showed no evidence of sonication-induced changes in AC. Consequently, spark-gap -generated sound may offer a solution for localized drug delivery into AC in a non-destructive fashion. Further research on this method may contribute to OA drug therapies.